Comparative effectiveness of faecal microbiota transplant by route of administration. Issue 4 (August 2017) - Gundacker, N.D.; Tamhane, A.; Walker, J.B.; Morrow, C.D.; Rodriguez, J.M.
Summary: The optimal route of delivery for faecal microbiota transplant (FMT) is unknown. This observational single-centre study analysed the two-week cure rates for all patients who received FMT from 2013 to 2016 according to route of delivery. Overall, nasogastric delivery of FMT was less effective than lower endoscopic delivery. When patients were stratified by illness severity, nasogastric delivery achieved similar cure rates in healthier individuals, whereas lower endoscopic delivery was preferred for relatively ill individuals. Nasogastric delivery may be less effective than lower endoscopic delivery; however, when taking the cost, preparation and potential risk into account, this difference may not be clinically significant for patients with mild disease.